Cardiovascular and temperature adverse actions of stimulants. (6th May 2021) - Docherty, James R.; Alsufyani, Hadeel A.
Abstract : The vast majority of illicit stimulants act at monoaminergic systems, causing both psychostimulant and adverse effects. Stimulants can interact as substrates or antagonists at the nerve terminal monoamine transporter that mediates the reuptake of monoamines across the nerve synaptic membrane and at the vesicular monoamine transporter (VMAT‐2) that mediates storage of monoamines in vesicles. Stimulants can act directly at presynaptic or postsynaptic receptors for monoamines or have indirect monoamine‐mimetic actions due to the release of monoamines. Cocaine and other stimulants can acutely increase the risk of sudden cardiac death. Stimulants, particularly MDMA, in hot conditions, such as that occurring at a "rave, " have caused fatalities from the consequences of hyperthermia, often compounding cardiac adverse actions. This review examines the pharmacology of the cardiovascular and temperature adverse actions of stimulants.